Personal impacts of using facebook and twitter on university students in Saudi Arabia - Huda AbdulAziz A, Aldegheiry (2016)
In recent year , there has been a rising trend in the u e of social networking. This phenomenon has positive and negative impacts on modem society including saudi Arabia is not in isolation from such impact. This study wa conducted to find out how university students use social networks, which include Facebook and Twitter. It also determine the per onal impact of social networking on t social relationships among university students in saudi Arabia and looking at the social networks' role in the promotion of cultural and religious identity of the university students.